A taxonomy of cognitive image functions for science curriculum materials: identifying and creating 'performative' visual displays. Issue 2 (22nd January 2021) - Peterson, Matthew; Delgado, Cesar; Tang, Kok-Sing; Bordas, Clément; Norville, Kayla
ABSTRACT: Pedagogical content knowledge of science teachers includes knowledge of representational forms, such as visual displays. Past research has provided a general means to evaluate pictures, but is not fine-grained on features internal to pictures. Furthermore, many existing picture function typologies consider pictures as subservient to text, though pictures have their own explanatory power. We here adapt a general 'performative' image function typology into a science-specific taxonomy of cognitive image functions with fine-grained distinctions of design strategies related to interpretative processes. The authors, including science educators and graphic designers, refined and expanded functions of imagery using visual displays in science textbooks following a constant comparison method. The resulting performative image function taxonomy consists of a structural framework that distinguishes conceptual elements internal to pictures (i.e. concepts, entities, components, attributes, adjuncts, configurations); a process model that identifies three interpretative phases necessary to understand visual displays (i.e. approach, activity, outcome); and 17 functions across the interpretative phases. We demonstrate these functions through analysis of and modifications to visual displays from science textbooks. Many of the modifications presented here can be repeated with rudimentary drawing over existing illustrations (e.g. arrows, dividing lines, labels), and they are thus accessible to science teachers and students.